Correlation of following components of culture peach palm and some chemical attributes of eutrochrept - Montanari, Rafael [UNESP]; Lima, Elizeu de Souza [UNESP]; Lovera, Lenon Henrique [UNESP]; Ferrari, Samuel [UNESP]; Queiroz, Hernandes Andrade [UNESP] (Univ Estadual Mato Grosso Sul, 2016)
The peach palm (Bactris gasipaes) has proven a great economical option for farmers because their palm production allows cutting precocity, rusticity, abundant tillering, tasty, no palm rust, high productivity and ease in cultivation. The objective was to select, between the soil properties, the one with the best correlation, linear and space to explain the variability of the peach palm plant. O experiment was conducted at the research farm, extent of Engineering College of Registro (SP) evaluated the spatial variability of the vegetative components of peach palm, and chemical properties of a Eutrophic Cambisol. A grid with 54 points was georeferenced to represent the entire sampling area of approximately 1.0 ha. Soil chemical properties presented variability from very high to low and plant properties had a mean variability too high. The average values of MO, P, Ca and Mg were found near suitable for the development of peach palm plant be explained by an exponential model is highly significant due to the spherical potassium and CTC.
Keywords: Bactris gasipaes; Soil management; geoestathistical; Ribeira Valley